Case Report: Endogenous Candida Endophthalmitis in Cornelia de Lange Syndrome: Atypical Stellate Neuroretinitis. Issue 2 (29th January 2021) - El Hamichi, Sophia; Kon Graversen, Veronica; Gold, Aaron S.; Berrocal, Audina M.; Murray, Timothy G.
Abstract : SIGNIFICANCE: This study aimed to highlight the association of stellate neuroretinitis occurring secondary to endogenous candidemia. PURPOSE: We report an unusual presentation of endogenous Candida endophthalmitis as a stellate neuroretinitis in the setting of Cornelia de Lange syndrome. CASE REPORT: A 34-month-old girl with severe Cornelia de Lange syndrome and a history of parenteral nutrition dependence requiring a chronic central venous catheter presented with bilateral endophthalmitis secondary to candidemia. In one eye, the endophthalmitis had the atypical presentation as a stellate neuroretinitis. CONCLUSIONS: This case represents a unique association of stellate neuroretinitis secondary to Candida infection in a patient with Cornelia de Lange syndrome.